Efficacy, safety, and genetic analysis of furmonertinib (AST2818) in patients with EGFR T790M mutated non-small-cell lung cancer: a phase 2b, multicentre, single-arm, open-label study. Issue 8 (August 2021) - Shi, Yuankai; Hu, Xingsheng; Zhang, Shucai; Lv, Dongqing; Wu, Lin; Yu, Qitao; Zhang, Yiping; Liu, Li; Wang, Xiang; Cheng, Ying; Ma, Zhiyong; Niu, Hongrui; et al.
Summary: Background: Furmonertinib (AST2818) is a third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) targeting both sensitising EGFR and EGFR Thr790Met (T790M) mutations. This study aimed to assess the efficacy and safety of furmonertinib in patients with EGFR T790M mutated advanced non-small-cell lung cancer (NSCLC). Methods: This study was a single-arm, open-label, phase 2b study at 46 hospitals across mainland China. Patients with locally advanced or metastatic NSCLC with centrally confirmed EGFR T790M mutations in tumour tissue who progressed after first or second generation EGFR TKIs or with primary EGFR T790M mutations received furmonertinib 80 mg orally once daily. The primary endpoint was objective response rate. Efficacy was assessed by blinded independent central review as per the Response Evaluation Criteria in Solid Tumors (version 1.1) in all patients who had measurable disease at baseline and received at least one dose of furmonertinib. Safety was assessed as per the Common Terminology Criteria for Adverse Events (version 4.03) in all patients who received at least one dose of furmonertinib with at least one safety assessment during follow-up. This study is registered with ClinicalTrials.gov (NCT03452592 ) and is ongoing for survival follow-up. Findings: From Jun 4, 2018, to Dec 8, 2018, 220 patients received furmonertinib treatment. All 220 patients were included in the efficacy and safety analyses. At the data cutoff point of Jan 29, 2020, 71 (32%) patients remained on treatment. The median duration of follow-up was 9·6 months (range 0·7–19·4). The objective response rate was 74% (163 of 220 [95% CI 68–80]). Grade 3 or higher adverse events occurred in 58 (26%) patients and treatment-related grade 3 or higher adverse events occurred in 25 (11%) patients. The most common all-cause grade 3 or higher adverse events were increased γ-glutamyltransferase (five; 2%), increased aspartate aminotransferase, increased alanine aminotransferase, hyponatraemia, hypertension, pulmonary infection, hypermagnesaemia, and pericardial effusion (three each; 1%). Treatment-related diarrhoea was reported in ten (5%) patients and rashes were reported in 16 (7%) patients, all grade 1–2. Serious adverse events were reported in 52 (24%) patients, of which 12 (5%) were possibly treatment-related as evaluated by the investigator. Interpretation: Furmonertinib has promising efficacy and an acceptable safety profile for the treatment of patients with EGFR T790M mutated NSCLC. Furmonertinib is expected to become a new treatment option after first or second generation EGFR TKIs in the Chinese population. Funding: Shanghai Allist Pharmaceutical Technology, Ministry of Science and Technology of the People's Republic of China, and Chinese Academy of Medical Sciences. Translation: For the Chinese translation of the abstract see Supplementary Materials section.